Acylation stimulating protein, complement C3 and lipid metabolism in ketosis-prone diabetic subjects. - Yan Liu; Priyanka Gupta; Marc Lapointe; Thewjitcharoen Yotsapon; Sunthornyothin Sarat; Katherine Cianflone (PLoS ONE, 2014)
Ketosis-prone diabetes (KPDM) is new-onset diabetic ketoacidosis without precipitating factors in non-type 1 diabetic patients; after management, some are withdrawn from exogenous insulin, although determining factors remain unclear.Twenty KPDM patients and twelve type 1 diabetic patients (T1DM), evaluated at baseline, 12 and 24 months with/without insulin maintenance underwent a standardized mixed-meal tolerance test (MMTT) for 2 h.At baseline, triglyceride and C3 were higher during MMTT in KPDM vs. T1DM (p<0.0001) with no differences in non-esterified fatty acids (NEFA) while Acylation Stimulating Protein (ASP) tended to be higher. Within 12 months, 11 KPDM were withdrawn from insulin treatment (KPDM-ins), while 9 were maintained (KPDM+ins). NEFA was lower in KPDM-ins vs. KPDM+ins at baseline (p = 0.0006), 12 months (p<0.0001) and 24 months (p<0.0001) during MMTT. NEFA in KPDM-ins decreased over 30-120 minutes (p<0.05), but not in KPDM+ins. Overall, C3 was higher in KPDM-ins vs KPDM+ins at 12 months (p = 0.0081) and 24 months (p = 0.0019), while ASP was lower at baseline (p = 0.0024) and 12 months (p = 0.0281), with a decrease in ASP/C3 ratio.Notwithstanding greater adiposity in KPDM-ins, greater NEFA decreases and lower ASP levels during MMTT suggest better insulin and ASP sensitivity in these patients.